Case report: abemaciclib-induced syndrome of inappropriate antidiuretic hormone (SIADH) without underlying kidney injury in a patient with early-stage estrogen receptor (ER)+ breast cancer - Carleton, Neil; Foldi, Julia (Frontiers in Medicine, 2024)
The CDK4/6 inhibitor, abemaciclib, is now the standard of care adjuvant therapy for patients with estrogen receptor-positive (ER+)/human epidermal growth factor receptor 2-negative (HER2-) tumors at high risk of recurrence. Real-world usage uncovers emerging side effects that may have been previously unreported in clinical trials. Here, we present the clinical course of a patient who developed a syndrome of inappropriate antidiuretic hormone (SIADH) without underlying kidney injury due to abemaciclib use.